Suggestibility and its Relationship to Psychological Needs among Sample of Drug Addicts in the Irada Complex in Jeddah - Al-Ghamdi, Samia Ahmed; Jamal Al-Layl, Muhammad Jafar (Journal of Educational and Psychological Sciences, 2025)
The purpose of the study was to investigate the relationship between suggestibility and psychological needs among a sample of drug addicts (76) male in the Irada Complex in Jeddah, Saudi Arabia. To achieve the objectives of the study, descriptive method (correlational and comparative) have been applied, and the scales of Suggestibility and Psychological Needs were administered. The data is then analyzed using correlation, step wis and one away analysis. The results indicates that negative relationship between suggestibility and psychological needs found, and no difference in both of them in terns of the period of addiction. The results were then discussed in the context of Saudi culture.The most important recommends are developing therapeutic and awareness programs that address the fulfillment of psychological needs and enhance self-awareness among individuals with substance use disorders. Continuous psychological support is also essential to prevent relapse. Furthermore, preventive programs should be implemented in schools and communities to reduce susceptibility to persuasion and equip individuals with effective coping skills for psychological pressures.